THE ROLE OF AI (ARTIFICIAL INTELLIGIENCE) IN TEACHING FOREIGN LANGUAGES - Ergashev Farrukhbek (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: The integration of artificial intelligence (AI) in foreign language education is revolutionizing the way languages are taught and learned. AI technologies, such as intelligent tutoring systems and natural language processing, provide personalized learning experiences that cater to individual student needs.